Ginzburg-Landau system of complex modulation equations for a distributed nonlinear-dispersive transmission line - Kengne, E.; Vaillancourt, R. (Нелінійні коливання, 2006)
The envelope modulation of a monoinductance transmission line is reduced to generalized coupled Ginzburg – Landau equations from which is deduced a single cubic-quintic Ginzburg – Landau equation containing derivatives with respect to the spatial variable in the cubic terms. We investigate the modulational instability of the spatial wave solutions of both the system and the single equation. For the generalized coupled Ginzburg – Landau system we consider only the zero wavenumbers of the perturbations whose modulational instability conditions depend only on the system’s coefficients and the wavenumbers of the carriers. In this case, a modulational instability criterion is established which depends both on the perturbation wavenumbers and the carrier. We also study the coherent structures of the generalized coupled Ginzburg – Landau system and present some numerical studies. Огортуючу модуляцiю моноiндуктивної лiнiї передач зведено до узагальнених пов’язаних мiж собою рiвнянь Гiнзбурга – Ландау, звiдки отримано одне рiвняння Гiнзбурга – Ландау третього – п’ятого порядку, яке мiстить похiднi вiдносно просторової змiнної в кубiчних членах. Для системи та рiвняння дослiджено модуляцiйну нестiйкiсть розв’язкiв у формi просторової хвилi. Для системи Гiнзбурга – Ландау розглянуто лише збурення з нульовими хвильовими числами, для яких умови модуляцiйної нестiйкостi залежать тiльки вiд коефiцiєнтiв системи та хвильових чисел носiїв. У цьому випадку отримано критерiй для модуляцiйної нестiйкостi, який залежить як вiд хвильових чисел збурень, так i вiд носiя. Також вивчаються когерентнi структури системи Гiнзбурга – Ландау та проведено деякий числовий аналiз.